Chambers, Claire. Making Sense of Contemporary British Muslim Novels. London: Palgrave Macmillan, 2019. 302 pp. - Chaoui, Saleh (FOCUS: Papers in English Literary and Cultural Studies, 2020)
In the period following the Rushdie affair, British Muslim literature came to prominence as a compelling contemporary literary tradition. Claire Chambers’s previous publications, among which British Muslim Fictions (2011), Britain through Muslim Eyes (2015), and Rivers of Ink (2017) are the best known, established her as a leading voice in Muslim literary studies. In Making Sense of Contemporary British Muslim Novels, a follow-up to Britain through Muslim Eyes, Chambers continues her project of examining the novelistic representation of the senses (touch, smell, taste, and hearing) in a rich fictional output by British Muslim authors. Chambers’s work is a groundbreaking monograph, for it adds a novel and valuable contribution to the exploration of British Muslim literature as it examines the ways in which the senses shape the reading practices of postcolonial writings. Drawing on a wide range of contemporary authors from a Muslim heritage in Britain whose works were especially strongly politicized in the years following the Rushdie affair, Chambers asserts that these post-Fatwa narratives, to a varying degree of religiosity, “are richly sensual” (xiv). Using a highly innovative critical methodology, the author expands the boundaries of the current scholarship on postcolonial literary criticism to include sensory studies. This leads to Chambers’s central argument: embracing sensation is an act of self-expression and resistance. Regarded as a double-edged sword, this resistance discloses “the marginalization or cover-up of non-heteronormative sexualities and women’s rights that sometimes occur in Muslim communities” (xxxii), and more pervasively, it fends off the increased attempts by the British government to surveil and control Muslim bodies.